2014
DOI: 10.1038/nchembio.1498
|View full text |Cite
|
Sign up to set email alerts
|

Design of activated serine–containing catalytic triads with atomic-level accuracy

Abstract: A challenge in the computational design of enzymes is that multiple properties must be simultaneously optimized -- substrate-binding, transition state stabilization, and product release -- and this has limited the absolute activity of successful designs. Here, we focus on a single critical property of many enzymes: the nucleophilicity of an active site residue that initiates catalysis. We design proteins with idealized serine-containing catalytic triads, and assess their nucleophilicity directly in native biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 41 publications
(51 reference statements)
1
62
0
Order By: Relevance
“…In a separate effort to create a toxin-neutralizing protein, a unique catalytic triad was computationally designed and subsequently optimized by yeast display. The resulting protein reacted with a fluorophosphonate probe at rates comparable to natural serine hydrolases, yet it was incapable of catalytic turnover [67]. …”
Section: Combining Directed Evolution With Rational Designmentioning
confidence: 99%
“…In a separate effort to create a toxin-neutralizing protein, a unique catalytic triad was computationally designed and subsequently optimized by yeast display. The resulting protein reacted with a fluorophosphonate probe at rates comparable to natural serine hydrolases, yet it was incapable of catalytic turnover [67]. …”
Section: Combining Directed Evolution With Rational Designmentioning
confidence: 99%
“…The designs are selected through computational modeling of transition-state analogues within side-chain constellations. 7,8 Iterative rounds of computational design, both in the active site and surrounding residues, place mutations to stabilize the transition state with the aim of accelerating the target reaction. Successes of this approach include redesigned proteins with activities for the Kemp elimination, 9 and the retroaldol 10 and Diels-Alder 11 reactions.…”
mentioning
confidence: 99%
“…Recent studies by Steinkellner et al have identified two proteins with previously unknown promiscuous ene-reductase activity through geometric comparison13. Whereas, Rajagopalan et al grafts a desired amino acid structure by de novo design protocols to create novel serine esterases14.…”
mentioning
confidence: 99%